Penggunaan Media Pembelajaran Interaktif sebagai Sumber Belajar dalam Pembelajaran Bahasa Indonesia Kelas II-A SDN 6 Menteng Kota Palangka Raya - Rifki Zakiyah (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2022)
Based on initial observations before conducting the research, the researcher found that teachers had not been using learning media. Therefore, this study aims to determine the effect of interactive media usage as a learning source in Bahasa Indonesia learning, specifically focusing on the topic of wise money usage, for Grade II-A students at SDN 6 Menteng. The method used in this research is an experimental research method. The design employed in this study is the One-group Pretest-Posttest Design. Pre-tests and post-tests were used to determine students' learning outcomes, which consisted of fill-in-the-blank questions. Then, the data were analyzed using the t-test for two means to determine the research results. Based on the calculation results, the average pre-test score was 54.5, and the average post-test score was 79.5, with a difference of 25 between the average pre-test and post-test scores. From the t-test for two means, the obtained t-value was 5.554, and the t-table value was 1.729 with a significance level of 5% and degrees of freedom (df) = 19. The criteria for the hypothesis were that the calculated t-value was greater than the table t-value, thus rejecting the null hypothesis (Ho) and accepting the alternative hypothesis (Ha). Therefore, it can be concluded that there is a positive influence of using interactive learning media on the learning outcomes of Grade II-A students at SDN 6 Menteng in Bahasa Indonesia learning, specifically on the topic of wise money usage.